Construction of binder-free hierarchical mesoporous 3D Co–Mo–O flowers assembled by nanosheets for aqueous symmetrical 1.2 V supercapacitor in basic electrolyte. (10th January 2020) - Javed, Muhammad Sufyan; Hussain, Shahid; Asim, Sumreen; Khan, Abdul Jabbar; Aslam, Muhammad Kashif; Hanif, Muddasir; Ahmad, Muhammad Ashfaq; Mai, Wenjie
Abstract: Aqueous symmetrical supercapacitors (ASSCs) are offering the safest and cost-effective solution to fulfill the ever-increasing demand for high-performance energy storage devices. However, the narrow operational voltage window in basic electrolytes is significantly limits their practical applications. Herein, we demonstrate a high-voltage ASSCs in a basic electrolyte by combining the binder-free highly Faradic-type cobalt and highly capacitive-type molybdenum oxides with rich oxidation/reduction states. The electrochemical performance of mesoporous cobalt-molybdenum oxide supported on carbon cloth (Co–Mo–O@CC) are first optimized in three electrode-system and it reveals high-capacitance of 1437.5 F g −1 (862.5 C g −1 ) at 1.5 A g −1 with outstanding rate-capability (81.19%) and cycling stability (95%) over 8000 cycles. Moreover, the fabricated ASSC based on the Co–Mo–O@CC electrodes (CMO||CMO-ASSC) is delivered admirable performance by exhibiting the high-capacitance of 180.5 F g −1 (2.63 F cm −2 ) at 1.0 A g −1 with good rate capability of 72.34% at high current density of 8 A g −1 as well as decent capacitance retention of 91.80% after 15000 cycles. The CMO||CMO-ASSC displayed a high energy density of 40.77 Wh kg −1 at a high-power density of 894.24 W kg −1 (based on the mass of active materials), which is the best value among ASSCs reported previously. Furthermore, the two CMO||CMO-ASSC coupled in series can charge up to 2.4 V and power two red color light-emitting-diodes (LEDs), demonstrating its practical applications as energy storage devices. Thus, this work paves a novel way to develop high-voltage ASSCs with large energy density and super long life energy storage devices. Graphical abstract: The CMO||CMO-ASSC displayed a high energy density of 40.77 Wh kg −1 at a high-power density of 894.24 Wh kg −1 (based on the mass of active materials), which is the best among the ASSCs reported previously. The two CMO||CMO-ASSC coupled in series can charge up to 2.4 V and power two red color light-emitting-diodes (LEDs), demonstrating its practical applications as energy storage devices. Image 1 Highlights: The binder-free cobalt molybdenum oxide (Co-Mo-O@CC) flowers are synthesized by eco-friendly method. The Co-Mo-O@CC revealed high-capacitance with outstanding rate-capability and cycling stability over 8000 cycles. The CMO||CMO-ASSC displayed a high energy density of 40.77 Wh kg −1 at a high-power density of 894.24 Wh kg −1 . Two CMO||CMO-ASSC coupled in series can charge up to 2.4 V and power two red color light-emitting-diodes.